Takhrij and Syarah Hadith of Agrotechnology: Humans Have a Role in Preserving the Earth - Ripni Marwiah; Wahyudin Darmalaksana; Muhammad Subandi (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with respect to humans in preserving the earth. This research method is qualitative through the takhrij and syarah hadith approaches. The results and discussion of this research are the activities of preserving the earth recommended by the Prophet Muhammad and are still developing until modern times. The conclusion of this research is that the activities of preserving the earth recommended by the Prophet Muhamad Saw based on the takhrij and sharah hadith of agrotechnology have many benefits.